Integrating Tarbiyah and Akhlaq in EFL Curriculum for Holistic Muslim Learner Development - Putri Rahayu Sulistiowati; Safarina Hidayati; Fara Dila; Intan Nuraini; Dewi Wijaya Putri; Nicha Chairunnisa Azahra; Zaitun Qamariah (Al-Mudarris, 2026)
The teaching of English as a Foreign Language (EFL) in Islamic educational institutions frequently adopts pedagogical materials developed within Western cultural contexts, which often reflect value-neutral or secular perspectives. While such materials may support linguistic competence, they may also implicitly transmit cultural norms that are not always aligned with the ethical and spiritual orientation of Islamic education. From the perspective of Islamic educational philosophy, education is not merely the transmission of knowledge but a holistic process aimed at nurturing faith (iman), moral character (akhlaq), and intellectual competence simultaneously. This study aims to conceptualize a framework for integrating Islamic educational values into the EFL curriculum in order to support the holistic development of Muslim learners. Using a systematic library research design, this study synthesizes more than twenty scholarly works on EFL pedagogy, curriculum studies, and Islamic educational philosophy. The analysis focuses on how principles such as tarbiyah, ta’dib, and moral development can guide curriculum integration in language education. The findings propose a four-level integration framework encompassing curriculum philosophy, instructional materials, teaching methodology, and assessment practices. The framework demonstrates that the integration of Islamic values can strengthen linguistic competence while simultaneously cultivating spiritual awareness, ethical responsibility, and reflective thinking. Ultimately, the study argues that EFL education in Islamic institutions should function as a means of developing ulul albab learners who combine intellectual excellence with moral integrity and spiritual consciousness.